THE VALUES OF ENTERPRENEURSHIP IN A MALAY CULTURE - Hasbullah, Hasbullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Work ethic is important in relation to work quality. In this paper, it is explained about the value of entrepreneurship in Malay culture. Sociologically, the authors argue that Malays have a fairly good entrepreneurial culture. Malay cultural values have roots that are closely related to Islamic values. While Islamic values are very clear in encouraging its people to trade culture. This can be traced in historical literature, for example Turner's opinion that Islam can only develop well in urban areas which are commercial and civilized.